IDEOLOGY OF POWER BY THE NETHERLANDS TOWARDS INDIGENOUS TO THE NOVEL MAX HAVELAAR BY MULTATULI - Indri Lestari (Prologue: Journal on Language and Literature, 2017)
Implementation of the policy carried out by the Dutch to the indigenousshow that domination conducted by the Netherlands could instill theideology that run at the time of colonialism. This study seeks to examinethe ideology of the Dutch, especially associated with political andeconomic policies, and their effect on indigenous people that oppressed,appear in the novel Max Havelaar by Multatuli as a research object.Researcher uses the theory of hegemony by Antonio Gramsci to analyzehow the party that has domination possesses an internal control to thesubordinates. Through deeper analysis, it is found that there are varieties ofpolitical and economic policies that automatically give bad effect for theoppressed indigenous, both physically and psychologically. Key words: hegemony, domination, indigenous